Iecehs 2018 2018
DOI: 10.3390/iecehs-1-05706
|View full text |Cite
|
Sign up to set email alerts
|

Risks for Population Health from Atmospheric Air Pollution in the City of Kazan

Abstract: The assessment of non-carcinogenic risk for the population health from chemicals coming from exhaust gases of motor transport citywide and in certain districts of the city of Kazan was performed. The calculation was carried out according to the results of the laboratory and instrumental tests carried out by “Center of Hygiene and Epidemiology in the Republic of Tatarstan” for the period from 2010 to 2016. The general toxic effect on the organs of the respiratory system from 42.5% to 62.0% in the city and distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“… 35 Frequent exposure can cause respiratory problems, decreased lung capacity, cardiovascular disease and mortality. 35 , 44 Some studies have shown a relationship between TSP and adverse health effects. 32 Location 5 was an area with the lowest hazard quotient value.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Frequent exposure can cause respiratory problems, decreased lung capacity, cardiovascular disease and mortality. 35 , 44 Some studies have shown a relationship between TSP and adverse health effects. 32 Location 5 was an area with the lowest hazard quotient value.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is a current global problem [1]. Exceeding the permissible emission values for harmful compounds and dust concerns large cities in particular [2][3][4] but also occurs locally in the nearest vicinity of the operated machines [5][6][7]. It is one of the reasons of dysphoria [8,9], loss of physical motion capacity [10], and health damage [11,12], and also contributes to the development of oncological diseases [13] and premature death [14,15].…”
Section: Introductionmentioning
confidence: 99%